1995
DOI: 10.7863/jum.1995.14.7.509
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of two distinct echogenic structures appearing on the same image using gain-assisted densitometric evaluation of sonograms (GADES).

Abstract: Gain‐assisted densitometric evaluation of sonograms with two distinct echogenic structures appearing on each image was performed to establish if their density‐gain setting curves have similar inclinations. We used the breast model (n = 67) in which hyperechoic masses were compared to the surrounding hyperechoic tissue at the optimal gain (Gopt) and at Gopt + 5. Both structures had significantly different film‐corrected densities and showed a linear decline of density as the system gain increased from Gopt ‐ 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Similarly, imaging a given tissue at a constant LC but at a different gain setting significantly changes the image density. These differences are greater than the dif ferences between fetal lung and liver or between fetal liver and bowel [2] and surely greater than the subtle differ ences between breast lesions and surrounding tissue [12]. Using relative echoes, i.e., comparing two echogenicities appearing on the same image, is commonly used to assess echogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, imaging a given tissue at a constant LC but at a different gain setting significantly changes the image density. These differences are greater than the dif ferences between fetal lung and liver or between fetal liver and bowel [2] and surely greater than the subtle differ ences between breast lesions and surrounding tissue [12]. Using relative echoes, i.e., comparing two echogenicities appearing on the same image, is commonly used to assess echogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Using relative echoes, i.e., comparing two echogenicities appearing on the same image, is commonly used to assess echogenicity. It has been shown that skewed values of image density are possible in comparing two distinct cchogenic structures appearing on the same image when produced in a given gain range [12], Moreover, we recent ly established that human vision is inadequate to discern isodensity or density differences in the range of those between fetal bowel and fetal liver [ 13].…”
Section: Discussionmentioning
confidence: 99%